2004
DOI: 10.1023/b:brea.0000021047.37869.95
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Versus Combined Treatment of Human Breast Cancer Cells with Antiestrogens and the Vitamin D Analogue EB1089 and Evaluation of Predictive Markers for Vitamin D Treatment

Abstract: Development of resistance to antihormonal therapy is a major problem in the treatment of breast cancer patients. Metastatic tumors, which progress after a period of response to treatment, often respond to second line endocrine treatment, but eventually develop estrogen independent growth. Vitamin D analogues are promising new drugs, using alternative mechanisms to inhibit growth of breast cancer cells. The sensitivity to antiestrogens and vitamin D analogues has been proposed to be inverse, indicating that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…It has previously been shown that Bcl-2 protein expression is lower in the majority of antiestrogen-resistant MCF-7 cell lines compared with parental MCF-7 cells (32,33). Figure 5A shows that the Bcl-2 protein level was lower in all eight antiestrogen-resistant cell lines investigated here compared with the MCF-7 cell line.…”
Section: Decreased Bcl-2 Level In Antiestrogen-resistant Cell Lines Imentioning
confidence: 57%
“…It has previously been shown that Bcl-2 protein expression is lower in the majority of antiestrogen-resistant MCF-7 cell lines compared with parental MCF-7 cells (32,33). Figure 5A shows that the Bcl-2 protein level was lower in all eight antiestrogen-resistant cell lines investigated here compared with the MCF-7 cell line.…”
Section: Decreased Bcl-2 Level In Antiestrogen-resistant Cell Lines Imentioning
confidence: 57%
“…Our studies complement the recent report by Miettinen et al (62) where CYP24 inhibition by VID400, a ketoconazole-like compound, enhanced the growth inhibitory effects of 1,25(OH) 2 D 3 in ovarian cancer cells. Similarly, Christensen et al (63) have reported that combined treatment of an antiestrogen with a 1,25(OH) 2 D 3 analogue was synergistic, abrogating the development of resistance in MCF-7 breast tumor cells in vitro.…”
Section: Discussionmentioning
confidence: 86%
“…Cell culture based experiments and laboratory animal experiments has clearly shown that 1α,25-dihydroxyvitamin D 3 is able to decrase the production and action of estrogens in breast cancer models, and also the growth of breast cancer xenotumors 70,[72][73][74][75]80 . Based on these findings, vitamin D or analogs has been proposed to be of potential use as an anti-cancer agent 76,[81][82][83][84] and a large number of clinical trials (e.g. ClinicalTrials.gov identifiers NCT00656019, NCT01472445, NCT01965522, NCT01948128, NCT01787409, and NCT01097278) are currently being conducted using vitamin D or analogs in different settings to investigate the potential use in the prevention or treatment of breast cancer.…”
Section: Discussionmentioning
confidence: 99%